In the uttermost East. Being an account of investigations among the natives and Russian convicts of the island of Sakhalin, with notes of travel in Korea, Siberia and Manchuria. With ills and maps (Scribner, 1904)
With index. Facsimile reprint: New York, Arno Press & The New York Times, 1970. (Russia observed. Advisory editors: H. Tupper and H.W. Nerhood).